Functional disorders of the respiratory system in combat chest injury - Olga I. Savushkina; Pavel A. Astanin; Maria M. Malashenko; Igor V. Pyhtin; Ekaterina R. Kuzmina; Andrey A. Zaitsev (ZAO "Consilium Medicum", 2023)
Background. Gunshot injuries occupy one of the leading places in a number of injuries (combat injuries) that occur in military conflicts. Aim. To study the effect of gunshot wounds of the chest (penetrating and non-penetrating), as well as closed chest trauma on the respiratory function. Materials and methods. The study included 78 patients with a diagnosis of combined trauma, including a gunshot penetrating/non-penetrating wound of the chest or closed chest injuries. The median period from injury to the time of lung function tests was 17 [15; 22] days. Results. A prospective cross-sectional study was performed. All patients (100% males) underwent spirometry, body plethysmography, and diffusion test. The total sample was divided into two groups: group 1 (median age 27.5 [23.0; 36.0] years) 68 patients with gunshot penetrating chest wound, group 2 (median age 26.5 [20.0; 30.5] years) 10 patients with gunshot non-penetrating wound or closed chest trauma. In group 1, the medians of the vital capacity, forced vital capacity, inspiratory capacity, forced exhalation volume in 1 second, lung diffusion capacity (determined by the value of the carbon monoxide transfer-factor DLCO) and alveolar volume were reduced. In group 2, pulmonary ventilation parameters were within normal values while the median of DLCO was reduced. There were no statistically significant differences between the groups. Conclusion. Both gunshot penetrating wounds of the chest and gunshot non-penetrating wounds of the chest and closed chest injuries have a negative impact, including on the respiratory function, to a greater extent on lung diffusion capacity. It is necessary to create programs of drug correction and longer rehabilitation treatment of this category of patients.